STRATEGI PEMBELAJARAN BAHASA ARAB DI MADRASAH ALIYAH SWASTA YAYASAN ISLAMIC CENTRE SUMATERA UTARA - Sukma Indriati; Wira Fitria; Devi Humairah Hayati; Mhd Hasan Basri Btr (Jurnal Sathar, 2023)
Learning Arabic is learning a foreign language which is known to be very difficult for beginner students to learn, even though in reality learning Arabic is easy. Any language learning requires a strategy in the learning process, and Arabic language learning strategies are an important approach in facilitating the process of mastering Arabic by students. This research aims to investigate various strategies that can be used in the context of learning Arabic, as well as their impact on achieving learning objectives. The research method used was descriptive qualitative involving a literature review to identify various learning strategies that have been proposed and implemented in Arabic language learning. The research results show that the strategy used is direct. Therefore, Arabic teachers need to understand the learning profile of each student and develop strategies accordingly. By understanding and applying these various Arabic language learning strategies, it is hoped that students can achieve a high level of fluency in communicating using Arabic, strengthen cultural understanding, understand the Al-Quran, hadith, or Arabic books, and improve their abilities in various communicative contexts.